Twin Deficits Hypothesis and Capital Mobility: The ASEAN-5 Perspective - Evan, Lau; Ahmad Zubaidi, Baharumshah; Hamizun, Ismail (Penerbit Universiti Kebangsaan Malaysia, 2009)
This paper investigates the relevance of the twin deficits hypothesis (TDH) in five Association of Southeast Asian Nations (ASEAN) countries. We examine the causal relation between current account deficits, budget deficits and investments. The empirical findings may be summarised as follows. First, TDH holds only for three countries: Malaysia, Thailand and the Philippines. In other words, a budget deficit plays a significant role in the determination of a current account deficit in all the three countries. Second, the findings are in line with the widely held view that government expenditure crowds out private investment. Third, investment shows a noticeable impact on current account deficits. Finally, a high proportion of domestic investment is financed from international sources, which suggests that the Feldstein-Horioka puzzle is less important in these emerging economies.